PENINGKATAN AKTIVITAS MENGGUNAKAN LABORATORIUM KOMPUTER DAN HASIL BELAJAR SISWA SMK PROGRAM KEAHLIAN AKUNTANSI MELALUI PENERAPAN PROJECT BASED LEARNING - David Firna Setiawan; Aryan Eka Prastya Nugraha (UNIVERSITAS MUHAMMADIYAH METRO, 2017)
The existence of the computer lab is one thing that is essential to support the improvement of students’ competence. Some other researcherssaid that some of the characteristics of PBL and its influence on motivation and learning outcomes, however, these studies can not describe the improvement of the activity in utilizing a computer lab. This study aimed to analyze the differences in the use of computer labs and student learning outcomes at the accounting program to operate accounting computer before and after the implementation of project based learning (PBL). The population of this study was all students of XI class and XII class in accounting programof SMK Al Falah Winong. Sampling in this study is using proportionate stratified random sampling. Data collected through observation. Hypothesis testing is done through t test with two independent samples. The results showed that the application of PBL was able to increase the activity in computer lab and student learning outcomes in the competence particularity on operate computer accounting application. Keywords: Project based learning, computer lab, Student learning outcomes